2020
DOI: 10.1186/s13052-020-0794-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal determinants in shaping offspring’s microbiome in the first 1000 days: study protocol and preliminary results at one month of life

Abstract: Background: Fetal programming during in utero life defines the set point of physiological and metabolic responses that lead into adulthood; events happening in "the first 1,000 days" (from conception to 2-years of age), play a role in the development of non-communicable diseases (NCDs). The infant gut microbiome is a highly dynamic organ, which is sensitive to maternal and environmental factors and is one of the elements driving intergenerational NCDs' transmission. The A.MA.MI (Alimentazione MAmma e bambino n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 61 publications
(74 reference statements)
2
26
0
Order By: Relevance
“…The intestinal colonization is believed to start in utero and adapt to numerous host and environmental factors. The host genetics plays a non-redundant role in shaping the intestinal microbiota ( Liso et al., 2019 ), nonetheless, several different factors further influence the composition of the gut microbiota including cesarean or natural birth, feeding types, weaning, birth environment, and mothers’ microbiota ( Nagpal et al., 2017 ; Raspini et al., 2020 ). As IBD patients, including mothers during pregnancy, are characterized by reduced α-diversity, it is not surprising that such reduction is transmitted to the offspring ( Torres et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal colonization is believed to start in utero and adapt to numerous host and environmental factors. The host genetics plays a non-redundant role in shaping the intestinal microbiota ( Liso et al., 2019 ), nonetheless, several different factors further influence the composition of the gut microbiota including cesarean or natural birth, feeding types, weaning, birth environment, and mothers’ microbiota ( Nagpal et al., 2017 ; Raspini et al., 2020 ). As IBD patients, including mothers during pregnancy, are characterized by reduced α-diversity, it is not surprising that such reduction is transmitted to the offspring ( Torres et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulated evidence indicates that microbiota development is shaped by host biology and related to the environment. Previous studies have shown that the composition of the intestinal flora of preterm infants was affected by many factors, such as maternal illness and nutritional status during pregnancy ( 20 ), delivery mode ( 21 ), feeding mode ( 22 , 23 ), gestational age ( 24 , 25 ), type and duration of antibiotic use ( 26 , 27 ), intrauterine or nosocomial infection ( 28 , 29 ), environment in NCU ( 30 ), use of probiotics and so on ( 31 , 32 ). In our study, we choose those infants that were deliverd by cesarean, no breastmilk feeding, no NEC or sepsis, no probiotics and asphyxia, so we did not analyze those factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The complete study design and the study protocol were previously described elsewhere (Raspini et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The intestinal microbiota undergoes dynamic development during the first years of life, determining adult microbiota composition and, consequently, impacting health. Many factors influence the shaping of gut microbiota in this critical window of plasticity, including gestational age, maternal pre-pregnancy BMI, weight gain during pregnancy, mode of birth, feeding types, weaning, birth environment, besides ethnic/geographical background (Nagpal et al, 2017;Raspini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%